2019
DOI: 10.3389/fvets.2019.00105
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Coping Capacity: An Integrative Parameter for Wildlife Welfare Within Conservation Interventions

Abstract: Wildlife management, conservation interventions and wildlife research programs often involve capture, manipulation and transport of wild animals. Widespread empirical evidence across various vertebrate taxa shows that handling wildlife generally induces a severe stress response resulting in increased stress levels. The inability of individuals to appropriately respond to rapidly changing environmental conditions during and after manipulations may have deleterious and long-lasting implications on animal welfare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 99 publications
1
20
0
Order By: Relevance
“…For the first time, we report a physiological response to restraint stress during the migratory period using LCC, where LCC levels significantly decreased with sampling time. In general and independently of life-history stages, low LCC levels and no recovery or a decrease in LCC within 30 min after a short-term stress event suggest high-stress levels and diminished capacity of the organism to effectively cope with and recover from stress (Huber et al 2019;McLaren et al 2003). The decline in LCC of the current study in all individuals is remarkable since captive house sparrows showed an increase in LCC, interpreted as a partial restoration of the capacity to cope with repeated or novel stress (Huber et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, we report a physiological response to restraint stress during the migratory period using LCC, where LCC levels significantly decreased with sampling time. In general and independently of life-history stages, low LCC levels and no recovery or a decrease in LCC within 30 min after a short-term stress event suggest high-stress levels and diminished capacity of the organism to effectively cope with and recover from stress (Huber et al 2019;McLaren et al 2003). The decline in LCC of the current study in all individuals is remarkable since captive house sparrows showed an increase in LCC, interpreted as a partial restoration of the capacity to cope with repeated or novel stress (Huber et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Other physiological pathways, such as the endocrineimmune interface may provide additional insights into stress associated trade-offs and biological costs but are rarely studied. Based on the observation that leukocytes of stressed individuals have a reduced capacity to produce reactive oxygen species (ROS) in response to a secondary (chemical) external stimulus, several studies on mammals have used a method called leukocyte coping capacity (LCC; leukocyte ROS production; McLaren et al 2003) as a proxy for stress (reviewed by Huber et al 2019). Recently, we showed in captive House Sparrows (Passer domesticus) that the immunological tool LCC may provide a more integrative perspective on the effects of stress rather than being just one of its constituent mediators (Huber et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…LCC has been suggested as a reliable and sensitive tool to measure stress in mammals and birds and has been successfully applied to assess psychological stress in humans (Mian and MacDonald, 2010; Shelton-Rayner et al, 2012). In respect to the existing literature, a decrease in the LCC response, or a lack of recovery respectively, is an indicator for high stress levels and a reduced capacity to cope with and/or recover from a stress event (Huber et al, 2019; McLaren et al, 2003). For instance, in captive house sparrows ( Passer domesticus ), leaving the birds undisturbed for 30 min in a cotton bag was sufficient to allow individuals to recover from capture stress in winter, reflecting in an increase of the measured LCC response (Huber et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of a stress response, the glucocorticoid-, α- and β-adrenoceptors of heterophil granulocytes are activated and an “oxidative burst”, is triggered, leading to the release of superoxide free radicals and the production of reactive oxygen species (ROS) (Frolov et al, 2006; Ronchetti et al, 2018). This reaction can be simulated under experimental conditions and measured in real-time via chemiluminescence from whole blood (Huber et al, 2020; Huber et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These activities induce stress, injury, sickness, and compromise immune systems. The multiple stressors inhibit animal immune responses and allow for enhanced shedding of pathogens ( 15 ). Stress also leads to increased excretion of saliva and voiding of urine and feces, all of which facilitate the shedding of viruses.…”
Section: The Wildlife Trade For Consumptionmentioning
confidence: 99%